PERAN GURU BIMBINGAN DAN KONSELING DALAM MEMBANTU PEMBENTUKAN NILAI KARAKTER SIKAP HORMAT DAN TANGGUNG JAWAB PESERTA DIDIK DI SMA NEGERI 7 KERINCI - Maria, Santa; Kasih, Fitria; Wira Nita, Rahma (Bimbingan dan Konseling, 2013)
This research is conducted by researchers discovered a phenomenon that is still found in the field, who was twice learners have problems related to value and respect the character does not have the value of responsibility. So the researchers raised the issue of research on the role of teachers in helping to establish the value of BK respect the character and responsibilities of students at SMAN 7 Kerinci. This research is descriptive research that seeks to describe the situation for what it is. The study population was all students at SMAN 7 Kerinci, amounts 713 people. Techniques used in sampling was multistage random sampling ie sampling using a sampling technique or method. The samples in this study were 73 respondents. The instrument used in this study was a questionnaire. As for the use of data analysis techniques percentage.The research results revealed that : (1) The role of counselors Â in helping to establish the value of BK comity character, ie treat others nicely categorized quite well, good manners towards others considered good enough , listen to what other people are categorized quite well, not insulting or making fun of other people categorized quite well, never threatened or forced on people requested category is quite good, and do not judge people before knew him pretty well categorized. (2) The role of counselors in helping to establish the value of responsibility characters, which is considered quite good reliable, do a good job is categorized something good, do not blame others well categorized and classified using mind before acting is quite good.